Ethnic inequalities in incidence, survival and mortality from abdominal aortic aneurysm in New Zealand. Issue 12 (5th July 2012) - Sandiford, Peter; Mosquera, Damien; Bramley, Dale
Abstract : Background: Ethnic variation in abdominal aortic aneurysm (AAA) incidence, survival and mortality is not well documented and yet has important equity implications for screening programmes. This study quantifies ethnic differences in hospital incidence, mortality and survival from AAA among Māori, Pacific, Asian and European/other ethnicities in New Zealand (NZ). Methods: Retrospective analysis of linked NZ hospital and death register records identified all patients admitted to a public hospital with a diagnosis of AAA and deaths from AAA from 1996 to 2007. Patients were grouped by ethnicity as Asian, Māori, Pacific or European/other. Results: Compared with the European/other group, Māori were 8.3 years younger at first admission, had higher mortality rates (RR=1.30, 95% CI 1.06 to 1.60 for men; RR=2.66, CI 2.13 to 3.31 for women), lower 1-year cumulative relative survival (60% vs 73% for men and 56% vs 67% for women; p<0.0001 for both) and were much less likely to have their aneurysm repaired electively (39.6% vs 61.1%; p<0.00001). Also, Māori women but not men were found to have a significantly higher standardised incidence rate (RR=1.56, 95% CI 1.37 to 1.79). In contrast, the incidence rate ratio for Asians (both men and women) was just 0.38 (95% CI 0.27 to 0.54 and 0.30 to 0.47, respectively) and both sexes also had a significantly lower mortality rate than European/other. Pacific men but not women also had a significantly lower incidence rate and frequency of aneurysm repair (40.0%; p=0.027). Conclusions: Ethnic variation in the incidence, mortality and cumulative relative survival from AAA in NZ resembles ethnic inequalities in other health outcomes. This provides additional support for screening on equity grounds.